Sustainable water use and the nexus of behavioural intentions: the case of four South African communities. (20th December 2017) - Onyenankeya, Kevin; Caldwell, Marc; Okoh, Anthony I.
Abstract: South Africa continues to ramp up public campaigns to rein in escalating water demand against the backdrop of dwindling and erratic supply. While the water conservation campaign appears to resonate with commercial and urban water users, it does not seem to have gained traction with rural and periurban residents. Using the sequential mixed methods, this paper explores the water conservation attitudes, behaviour and intentions of rural and periurban respondents in four South African communities. Results reveal respondents consider water conservation important and are favourably disposed to conserving water. Attitude, subjective norm and behavioural control emerged as significant factors influencing respondents' water conservation intentions. The study concludes that rural and periurban residents are yet to develop a social ethic of water conservation essential in creating sustainability of resource use.